Relative Preference of Red Pumkin Beetle Aulacophora (RAPHIDOPALPA) Foveicollis (LUCAS) to Different Cucurbits - Pareek, B L; Kavadia, V S (Annals of Arid Zone, 2016)
Relative preference of red pumpkin beetle, AulacopllOra (Raphidapalpa) foveicollis (Lucas) was studied on ten field grown cucurbits both at Udaipur and Jobner. Musk melon, long melon and pumpkin were the most preferred hosts, bottle gourd and rigde gourd were the preferred hosts and sponge gourd and cucumber were only moderately preferred. Bitter gourd, round gourd and water melon were non-preferred hosts.